Efficacy of different modules for the management of major pests of tomato (Lycopersicon esculentum) and garden pea (Pisum sativum) in Himalayas - J.C. BHATT, N.K. HEDAU and H.S. GUPTA, K.S. HOODA*, S.N. SUSHIL, D. JOSHI (Indian Phytopathology, 2012)
Foliar and soil borne diseases are major impediments in profitable cultivation of garden pea and tomato in North West Himalayas. Therefore, three modules (IPM, Chemical and organic) were tested in hill ecosystem for pest management in garden pea and tomato. Out of 3 modules tested in tomato, maximum severity of early blight, buckeye rot and fruit borer was observed in organic module (>6.8%) followed by chemical (>4.4%) and IPM modules (>2.1%). Highest percent pest control on pooled mean basis was recorded by IPM module (> 82%) followed by chemical (> 33%) and organic module (> 55%) leading to significant yield enhancement (22.8% in organic, 67.5% in chemical and 105.3% in IPM modules) over their respective unprotected checks. The yield loss due to insect pests and diseases in organic, chemical module, organic unprotected check, chemical treated check and unprotected inorganic check compared to IPM module was 38.6%, 18.4%, 50.0%, 45.0% and 51.3% respectively. Benefit cost ratio ranged from 2.65 to 6.94 in the modules highest being IPM module (6.94). Amongst the 3 modules applied in garden pea, maximum incidence of pre-emergence rot, wilt, white rot, leaf blight, rust, ascochyta blight, powdery mildew, leaf miner and fruit borer were observed in organic module followed by IPM and chemical modules. Maximum percent pest control on pooled mean basis was in case of chemical module (>35%) followed by IPM (>27%) and organic module (>29%). All the modules led to significant yield enhancement (39%) in organic, 88.6% in chemical and 80.7% in IPM modules) over their respective unprotected checks. The yield loss due to pests in organic, IPM over chemical module was 32.4% and 4.2% respectively.